Effect of centrifugation time on growth factor and MMP release of an experimental platelet-rich fibrin-type product. (3rd July 2016) - Eren, Gülnihal; Gürkan, Ali; Atmaca, Harika; Dönmez, Ayhan; Atilla, Gül
Abstract: Platelet-rich fibrin (PRF) has a controlled release of growth factors due to the fibrin matrix structure. Different centrifugation protocols were suggested for PRF preparation. Since the derivation method of PRF can alter its contents, in the present study it is aimed to investigate the cell contents and transforming growth factor beta-1 (TGF-β1), platelet-derived growth factor (PDGF-AB), vascular endothelial growth factor (VEGF), matrix metalloproteinase (MMP)-1 and-8 release from experimental PRF-type membranes obtained with different centrifugation times at 400 gravity. Three blood samples were collected from 20 healthy non-smoker volunteers. One tube was used for whole blood analyses. The other two tubes were centrifuged at 400 g for 10 minutes (group A) or 12 minutes (group B). Each experimental PRF-type membrane was placed in Dulbecco's Modified Eagle's Medium (DMEM)and at 1, 24 and 72 hours, TGF-β1, PDGF-AB, VEGF, MMP-1 and -8 release amounts were analysed by enzyme-linked immunosorbent assay (ELISA). The blood cell count of membranes was determined by subtracting plasma supernatant and red blood cell (RBC) mixture from the whole blood cell counts. At 72 hours, the VEGF level of group B was statistically higher than that of group A ( p = 0.040). The centrifugation time was not found to influence the release of other growth factors, enzymes and cell counts. Within the limits of the present study, it might be suggested that centrifugation time at a constant gravity has a significant effect on the VEGF levels released from experimental PRF-type membrane. It can be concluded that due to the importance of VEGF in the tissue healing process, membranes obtained at 12-minute centrifugation time may show a superior potential in wound healing.